Building Nationalist-Religious Character through Mosque Youth Organizations: Insights from Senior High Schools in Bandung, Indonesia - Rifa Anggyana; Kokom Komalasari; Prayoga Bestari; Syaifullah Syaifullah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Character education is a strategic agenda in Indonesia’s nation-building, particularly in responding to globalization, moral degradation, and youth intolerance. Within secondary education, religious extracurricular organizations such as the Mosque Youth Association (Ikatan Remaja Masjid) play a vital role in fostering religiosity while strengthening nationalism. This study investigates the role of the Mosque Youth Association in cultivating nationalist-religious character among students in three high schools in Bandung. Methodology: Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, document analysis, and field notes. Seventeen respondents were selected purposively: school principals, association mentors, leaders, members, government officials, and academic experts. Data analysis employed Miles and Huberman’s interactive model data reduction, data display, and conclusion drawing validated through triangulation of sources, techniques, and time. Main Findings: The findings indicate that the Mosque Youth Association functions as a behavioral laboratory, shaping students’ nationalist-religious character through regular activities such as religious studies, congregational prayers, social service, and leadership training. Consistent habit formation occurs through positive reinforcement (recognition, trust, leadership opportunities) and negative reinforcement (warnings, social sanctions). Key challenges include fluctuating participation, limited resources, repetitive content, and digital demands addressed through program innovation, collaboration, and technology use. Novelty/Originality of this study: The study concludes that character development through the Mosque Youth Association aligns with behavioristic learning theory and provides insights for reinforcement-based character education compatible with the Merdeka Curriculum and the Pancasila Student Profile.